Species identification in forensic samples using the SPInDel approach: A GHEP-ISFG inter-laboratory collaborative exercise - Alves, Cíntia (2017)
DNA is a powerful tool available for forensic investigations requiring identification of species. However, it is necessary to develop and validate methods able to produce results in degraded and or low quality DNA samples with the high standards obligatory in forensic research. Here, we describe a voluntary collaborative exercise to test the recently developed Species Identification by Insertions/Deletions (SPInDel) method. The SPInDel kit allows the identification of species by the generation of numeric profiles combining the lengths of six mitochondrial ribosomal RNA (rRNA) gene regions amplified in a single reaction followed by capillary electrophoresis. The exercise was organized during 2014 by a Working Commission of the Spanish and Portuguese-Speaking Working Group of the International Society for Forensic Genetics (GHEP-ISFG), created in 2013. The 24 participating laboratories from 10 countries were asked to identify the species in 11 DNA samples from previous GHEP-ISFG proficiency tests using a SPInDel primer mix and control samples of the 10 target species. A computer software was also provided to the participants to assist the analyses of the results. All samples were correctly identified by 22 of the 24 laboratories, including samples with low amounts of DNA (hair shafts) and mixtures of saliva and blood. Correct species identifications were obtained in 238 of the 241 (98.8%) reported SPInDel profiles. Two laboratories were responsible for the three cases of misclassifications. The SPInDel was efficient in the identification of species in mixtures considering that only a single laboratory failed to detect a mixture in one sample. This result suggests that SPInDel is a valid method for mixture analyses without the need for DNA sequencing, with the advantage of identifying more than one species in a single reaction. The low frequency of wrong (5.0%) and missing (2.1%) alleles did not interfere with the correct species identification, which demonstrated the advantage of using a method based on the analysis of multiple loci. Overall, the SPInDel method was easily implemented by laboratories using different genotyping platforms, the interpretation of results was straightforward and the SPInDel software was used without any problems. The results of this collaborative exercise indicate that the SPInDel method can be applied successfully in forensic casework investigations.